PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SEMEN TONASA (PERSERO) KABUPATEN PANGKEP - Zainal Abidin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the variable labor discipline and motivation to work on the performance of employees at PT. Semen Tonasa (Persero) Pangkep. This study is a survey research. The population in this study were all employees of PT . Semen Tonasa (Persero) in the civil service Tonasa Unit IV 102 people. The number of samples determined by using Slovin approach as many as 50 people . The analysis model is a multiple linear regression model . The results showed that the discipline of work and work motivation significant effect partially and simultaneously on employee performance, in which motivation is the dominant factor that affects the performance of employees of PT. Semen Tonasa (Persero) Pangkep, with a fairly high degree of prediction, which is 0.582 (58.2 %)